DIGITAL GAMES IN DIGITAL LEARNING ENVIRONMENT; WHAT MAKES THEM EFFECTIVE IN EMBODYING VOCABULARY MASTERY - ovilia, ririn; warat, rofinus daton (English Department of Faculty of Tarbiyah and Teacher Training, 2016)
The rapid development of technology has triggered several changes in the realm of education which significantly contribute to language instruction. One of the changes is the integration of digital games in vocabulary learning. Digital games, either online or offline, have become inseparable from students? daily life. A number of students playing games are exceptionally growing in many countries. Due to this fact, the researchers and practitioners have been stimulated to investigate the effects of digital games on language learning, particularly in vocabulary learning. Thus, a lot of studies have been carried out to find out the effectiveness of this integration. This paper aims to discuss the aforementioned studies as the insights to give empirical evidence on how digital games enhance students? vocabulary mastery and what makes them effective to be used in the learning process. Besides, it also attempts to succinctly delineate the challenges, the threats that might occur during the learning process, and some considerations to be noted by the teachers such as the selection of the games, the tasks, and the rules in using the technological devices.